2018
DOI: 10.1016/s2468-1253(17)30284-4
|View full text |Cite
|
Sign up to set email alerts
|

Restrictions for reimbursement of interferon-free direct-acting antiviral drugs for HCV infection in Europe

Abstract: All-oral direct-acting antiviral drugs (DAAs) for hepatitis C virus, which have response rates of 95% or more, represent a major clinical advance. However, the high list price of DAAs has led many governments to restrict their reimbursement. We reviewed the availability of, and national criteria for, interferon-free DAA reimbursement among countries in the European Union and European Economic Area, and Switzerland. Reimbursement documentation was reviewed between Nov 18, 2016, and Aug 1, 2017. Primary outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 43 publications
(48 reference statements)
0
118
0
Order By: Relevance
“…Despite the availability of generic and low‐cost DAAs in some resource limited settings, costs of DAA therapy in the vast majority of countries remains a barrier to widespread scale‐up of HCV treatment . Greater market transparency and price negotiations are required . Broad access to HCV treatment without restrictions: Modelling studies indicate that restricting treatment for those with more advanced fibrosis and/or by drug use status, as is occurring in many settings , will likely have limited impact on preventing transmission among PWID populations , the vast majority who are younger with less advanced disease. In settings where HCV epidemics are predominantly PWID‐driven, broad access to HCV treatment regardless of disease stage is therefore required for HCV elimination.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the availability of generic and low‐cost DAAs in some resource limited settings, costs of DAA therapy in the vast majority of countries remains a barrier to widespread scale‐up of HCV treatment . Greater market transparency and price negotiations are required . Broad access to HCV treatment without restrictions: Modelling studies indicate that restricting treatment for those with more advanced fibrosis and/or by drug use status, as is occurring in many settings , will likely have limited impact on preventing transmission among PWID populations , the vast majority who are younger with less advanced disease. In settings where HCV epidemics are predominantly PWID‐driven, broad access to HCV treatment regardless of disease stage is therefore required for HCV elimination.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the high list price of DAAs, our current reimbursement criteria are limited to patients with advanced liver diseases. Such restrictions for reimbursement are also commonly found in many high to moderate‐income countries which do not have access to generic DAAs . Therefore, a comprehensive population‐based epidemiological data are urgently needed to clarify the scope of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…NSPs can contribute substantially to reducing transmission of blood‐borne viruses among PWID , yet less than one‐third of study countries were reported to have NSPs available in all parts of their countries in 2017. The presence of injecting drug use‐related restrictions on access to DAAs for the treatment of HCV in several study countries is also a matter of concern, and other research has similarly documented such restrictions . European and global experts concur that injecting drug use does not constitute a valid reason for withholding treatment – indeed, global HCV elimination strategies depend on the reductions in transmission that are expected to occur when large numbers of chronically HCV‐infected people who currently inject drugs are cured with DAAs .…”
Section: Discussionmentioning
confidence: 99%